Enhancing the introverted student’s algebraic thinking through peer teaching with gusjigang wisdom: single subject research - Malasari, Putri Nur; Widodo, Sri Adi (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to examine the influence of peer teaching that incorporates the local wisdom of gusjigang on the algebraic thinking skills of the student with introverted personality. Method: The research employed a descriptive quantitative approach with a Single Subject Research (SSR) A-B design. The participant was a second-semester mathematics student identified as an introvert. Data were collected through tests, observations and interviews. Analysis was conducted by comparing two phases: the baseline and the intervention. The within-phase analysis considered factors, such as interval duration, trend direction, stability, rate of change and data patterns. The between-phase analysis explored differences in variable values, trend shifts and changes in data levels across the two phases. Findings: The results demonstrate that peer teaching based on gusjigang local wisdom has a positive impact on the algebraic thinking abilities of the introverted student. This is reflected in the increase in the subject’s average score from 21.5 before the intervention to 68.5 after the intervention was implemented. Significance: The implementation of peer teaching infused with local wisdom plays an important role in encouraging introverted students to become more engaged in learning. By creating a more inclusive and supportive classroom environment, this approach helps to improve the algebraic thinking skills of students who are typically less active during mathematics instruction.